2015
DOI: 10.1080/23311932.2015.1063829
|View full text |Cite
|
Sign up to set email alerts
|

Cotton fertilization using PGPR Bacillus amyloliquefaciens FZB42 and compost: Impact on insect density and cotton yield in North Benin, West Africa

Abstract: This work has compared the effects of the biofertilizer Bacillus amyloliquefaciens FZB42 with that of compost for cotton production. The population dynamics of pests and predators have been studied in order to check whether the use of both fertilization materials can contribute to pest management in cotton. Three treatments were considered: (i) dressing of seeds in rhizobacteria suspension, (ii) introduction of rhizobacterial suspension directly in the pocket, same time with the seeds, and (iii) fertilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
1
1
0
2
Order By: Relevance
“…mongolica seedlings increased signi cantly after PGPR inoculation, which was consistent with previous results whereby the PGPRs Serratia proteamaculans 1-102 and Serratia liquefaciens 2-68 could promote the emergence and growth of corn (Pan et al 1999). Thiery et al found that the PGPR Bacillus amyloliquefaciens FZB 42 could promote cotton growth (Alavo et al 2015), indicating that PGPRs can effectively promote plant growth.…”
Section: Discussionsupporting
confidence: 88%
“…mongolica seedlings increased signi cantly after PGPR inoculation, which was consistent with previous results whereby the PGPRs Serratia proteamaculans 1-102 and Serratia liquefaciens 2-68 could promote the emergence and growth of corn (Pan et al 1999). Thiery et al found that the PGPR Bacillus amyloliquefaciens FZB 42 could promote cotton growth (Alavo et al 2015), indicating that PGPRs can effectively promote plant growth.…”
Section: Discussionsupporting
confidence: 88%
“…Further investigations on bacterial root colonization would be of importance to ensure establishment and presence of different bacteria strains. Application strategy ( Alavo et al, ), a combination of different bacteria strains ( Liu et al., ), used substrate ( Fröhlich et al, ), P and N fertilization rate ( Zabihi et al, ; El Husseini et al, ; Afzal et al, ), specific N form contained in the N fertilizer ( Nkebiwe et al, ), and plant species ( Wang et al, ) are issues that could be varied in further experiments, while keeping in mind that experiments with living bacteria face limitations due to natural variation ( Tailor and Joshi , ).…”
Section: Discussionmentioning
confidence: 99%
“…L"effet bio-fertilisant de cette rhizobactérie s"est également manifesté dans un système de production de coton biologique. En effet, dans une étude visant à comparer l"effet de B. amyloliquefaciens FZB 42 avec celui du compost, on a obtenu une augmentation du rendement en coton-graine de l"ordre de 39% au niveau des plants traités avec la rhizobactérie puis fertilisés au compost (Alavo et al, 2015). On peut donc estimer que B. amyloliquefaciens FZB 42 peut être utilisée dans tous les systèmes de production cotonnière.…”
Section: Discussionunclassified